The case of tomato in Ghana: Marketing - Robinson, Elizabeth J. Z.; Kolavalli, Shashidhara (International Food Policy Research Institute, 2010)
In Ghana, the agricultural sector in general and the tomato sector in particular have not met their potential. In the tomato sector, production seasonality, the dominance of rainfed agriculture, high perishability of the fruits combined with no storage facilities, and poor market access, have resulted in low average yields but seasonal gluts with some farmers unable to sell their tomatoes which are consequently left to rot in their fields. The tomato value chain in Ghana is characterised by a “two level” system in which itinerant traders—the market queens —are the direct link between rural farm producers and urban consumption, rather than by a set of assembly markets which bulk the produce before being sold to urban wholesalers at relay markets. Assembly markets enable inspection, grading, and better price transmission, but the time taken to get the crop from farmgate to consumer is relatively long. The two-level trader system reduces delays of passing through assembly markets, allowing rapid movement of the produce from producer to consumer, important for highly perishable agricultural products such as tomato, but fragments price signals resulting in poor spatial price adjustments (Bell et al.1999; Orchard and Suglo 1999). In a two level system, farmers are distanced from market signals: most wait for the market queens to come to their fields and if these traders do not come, farmers leave the tomatoes to rot in the field in the absence of a local market. Traders allocate a certain number of crates, which determines how much farmers can sell on that particular day and there is little if any room for price-quantity or price-quality negotiations. Signals from consumers with respect to quality, price, and quantities demanded, are not transmitted back along the value chain to the farmers. Though packers may remove the poorest quality fruits, tomatoes of different qualities and even different varieties are not graded but rather simply piled them into over-sized crates.